MANAGEMENTUL PERFORMANȚEI ÎN ORGANIZAȚII - Zelenschi, Angela (CEP USM, 2023)
This article approaches the concept of performance management from the perspective of strategic management of organisations. The features of team effectiveness and personal effectiveness are presented. The need to ensure lasting success in the work of organisations by improving team performance and individual performance is demonstrated.
ERFORMANCE MANAGEMENT IN ORGANIZATIONS
ZELENSCHI, Angela. Managementul performanței în organizații. In: Teoria și practica administrării publice: materiale ale conferinței ştiințifico-practice internaționale, ediţia a 27-a, 19 mai 2023, Chişinău. Chişinău: Centrul Editorial-Poligrafic al USM, 2023, pp. 248-254.
Keywords: performance management; team effectiveness; personal effectiveness